Mutations in RPSA and NKX2‐3 link development of the spleen and intestinal vasculature. Issue 1 (23rd September 2019) - Kerkhofs, Chantal; Stevens, Servi J. C.; Faust, Saul N.; Rae, William; Williams, Anthony P.; Wurm, Peter; Østern, Rune; Fockens, Paul; Würfel, Christiane; Laass, Martin; Kokke, Freddy; Stegmann, Alexander P. A.; et al.
Abstract: Idiopathic intestinal varicosis is a developmental disorder defined by dilated and convoluted submucosal veins in the colon or small bowel. A limited number of families with idiopathic intestinal varices has been reported, but the genetic cause has not yet been identified. We performed whole‐exome and targeted Sanger sequencing of candidate genes in five intestinal varicosis families. In four families, mutations in the RPSA gene were found, a gene previously linked to congenital asplenia. Individuals in these pedigrees had intestinal varicose veins and angiodysplasia, often in combination with asplenia. In a further four‐generation pedigree that only showed intestinal varicosities, the RPSA gene was normal. Instead, a nonsense mutation in the homeobox gene NKX2‐3 was detected which cosegregated with the disease in this large family with a LOD (logarithm of the odds) score of 3.3. NKX2‐3 is a component of a molecular pathway underlying spleen and gut vasculature development in mice. Our results provide a molecular basis for familial idiopathic intestinal varices. We provide evidence for a relationship between the molecular pathways underlying the development of the spleen and intestinal mucosal vasculature that is conserved between humans and mice. We propose that clinical management of intestinal varices, should include assessment of a functional spleen.